INVESTIGATION OF LIFELONG LEARNING AWARENESS AND SELF-CONSCIOUSNESS OF UNDERGRADUATES OF HEALTH SCIENCES - Caner KARARTI; Öznur BÜYÜKTURAN; Caner KARARTI; Buket BÜYÜKTURAN; Gamze EKİCİ (International Journal of Eurasia Social Sciences, 2018)
Background: At the heart of the concept of lifelong learning (LLL) is the continual development of an individual’s competences. A post-graduate education (PGE) is a process that contributes to an individual’s LLL. The high self-consciousness (SC) of an individual is also important to succeed in PGE. The aim of this study is to examine the awareness of Health Sciences (HS) undergraduate students towards LLL and its relationship with the SC. Materials and Methods: A total of 184 individuals, 90 female and 94 male, were included in the study. Individuals’ awareness of LLL, and SC, was assessed by LLL tendency scale, and SC scale, respectively. Their awareness of PGE, however, was evaluated using a questionnaire developed by the researchers. Results: There was no statistically significant correlation between the total score of the LLL scale (p = 0.199) and the total score of the SC scale (p = 0.215) with the students’ grades. There was no statistically significant relationship between level of knowledge about PGE and the questionnaire (p = 0.532). It was found that the percentage of individuals responding correctly to the questions in the questionnaire developed by the researchers and the participation rate in the examinations required for the PGE did not increase with the participants’ grades. This percentage was higher in 2nd grade compared to the 3rd, 2nd compared to the 4th, and 4th compared to the 1st grade. Conclusion: According to the results of this study, higher grades of HS undergraduate students is not related to their awareness of LLL, SC and the level of their knowledge about PGE.